A quality improvement initiative to augment success rate of labour analgesia: interrupted time series analysis - Panta, SB; Bhattarai, PR; Sharma, A; Basnet, U; Khadka, R; Pradhan, K (Nepal Mediciti Medical Journal, 2024)
BACKGROUND Standard operating procedures (SOP) for abour analgesia for parturients in Nepal are lacking. Labour analgesia programme was being conducted without a SOP in our institution. We identified that the success rate of epidural labour analgesia (ELA) was low. We developed standard operating procedures for labour analgesia services with the combined effort of the department of anesthesia and pain management with the department of obstetrics and gynaecology in Nepal Mediciti in 2019 January. SOP and troubleshooting protocol was implemented in 2019 February and this study was conducted to investigate the impact of programmed protocol for labour analgesia. METHODS An interrupted time-series analysis was performed as a process improvement project for all cases who demanded labour analgesia from November 2017 to December 2019 with retrospective data collection. The success of epidural labour analgesia was defined as vaginal delivery with Numerical Rating Scale for labour pain of 3 or less. The time series analysis intended to identify the change in the level of success rate (increase or decrease) and change in the slope of success rate over time. RESULTS The major problems identified by the team included lack of patient counselling, inadequate followup after the first dose of epidural, delay in attending call for labour analgesia by the anesthesiologist and undefined clinical pathways for the usage of drugs and troubleshooting. After implementation of the protocol, the interrupted time series showed a 24.77% relative increase in success rate with p value <0.001. CONCLUSION Interdepartmental group discussions, interviews with the patients and development of a team that worked on formulating SOP was done after problem identification. Patient counselling after 28 weeks of gestation gave patients time for psychological preparation and have realistic expectations regarding ELA than labouring parturients. Clear protocol regarding drug dosing and troubleshooting disposed interpersonal variation among the anesthesiologists. Continuous patient follow-up by the nurse-led team helped to identify any additional problems and address it and add on to the protocol. In conclusion, standard operating procedures guided epidural labour analgesia programme enhanced the success rate of epidural labour analgesia.